Clinical features and prognostic value of stent-graft-induced post-implantation syndrome after thoracic endovascular aortic repair in patients with type B acute aortic syndromes. (20th October 2015) - Gorla, Riccardo; Erbel, Raimund; Kahlert, Philipp; Tsagakis, Konstantinos; Jakob, Heinz; Mahabadi, Amir-Abbas; Schlosser, Thomas; Eagle, Kim; Bossone, Eduardo; Jánosi, Rolf Alexander
Abstract : OBJECTIVES: The aim of this study was to investigate the incidence, the biomarker profile and the clinical impact of post-implantation syndrome (PIS) after thoracic endovascular aortic repair (TEVAR) for type B acute aortic syndromes (AASs). METHODS: This retrospective study included 133 patients with type B AASs undergoing TEVAR; PIS was defined as fever >38°C, white blood cells (WBCs) >12.0/nl and C-reactive protein (CRP) >10 mg/dl within 72 h after TEVAR, despite negative blood cultures. Fibrinogen (FBG), D-dimer (D-d) and interleukin 6 (IL-6) were also determined. The clinical endpoints were all-cause mortality and a composite of major adverse events (MAEs such as aortic rupture, need for reintervention and all-cause mortality) at follow-up. RESULTS: PIS was diagnosed in 15.8% of patients and was associated with higher peak values of WBC (17.0 ± 5.1 vs 10.6 ± 3.7/nl, P = 0.002), CRP (22.0 ± 5.4 vs 16.8 ± 8.2 mg/dl, P = 0.03), FBG (779 ± 246 vs 639 ± 225 mg/dl, P = 0.046), D-d (1675 ± 605 vs 1048 ± 639 µg/l, P = 0.003) and IL-6 (192 ± 101 vs 84 ± 34 pg/ml, P = 0.03) than non-PIS patients. All-cause mortality did not significantly differ between PIS and non-PIS patients during the index hospitalization (0.0 vs 6.3%; P = 0.60) and at follow-up (18.8 vs 4.9%; P = 0.086). MAEs were more frequent in the PIS than in the non-PIS group (62.5 vs 25.9%; P = 0.004). PIS (hazard ratio [HR] 3.26, P = 0.022), stroke (HR 3.41, P = 0.004), aortic enlargement (HR 6.88, P = 0.001) and partial thrombosis of the false lumen (HR 6.20, P = 0.003) were independent predictors of MAEs. CONCLUSIONS: PIS occurred in 15.8% of patients with AASs without affecting in-hospital outcome. At follow-up, PIS was associated with increased rates of MAEs, but not mortality.